Rocky 3. - Stallone, Sylvester (Pasig City : Viva Video.)
Rocky battles his most powerful adversary yet - the ferocious Clubber Lang, played by none other than Mr. T! For what may be the most exciting and fast-paced film in the series, Sylvester Stallone writes, directs and star with explosive passion and intensity. A Rocky Balboa (Stallone) fights his way into the hearts of millions, life couldn't be better. He scores ten consecutive wins, lands lucrative endorsements contracts and becomes famous the world over. But when Clubber Lang K.O..s Rocky in a humiliating defeat, it becomes apparent that he has lost his edge. Considering hanging up his gloves, Rocky receives encouragement from an unlikely ally: his old nemesis, Apollo Creed (Carl Weathers). With Creed's help, Rocky strives to regain the "eye of the tiger" before confronting Lang in a gruelling rematch for the world heavyweight championship. Featuring strong performances by Talia Shire, Burgess Meredith, Burt Young and Hulk Hogan, this hard-hitting actioner comes out swinging with adventures, humor and emotionally charged human drama.